2010
DOI: 10.1177/0192513x10386305
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of Lareau’s Qualitative Conclusions About Class, Race, and Parenting

Abstract: The authors used the Early Childhood Longitudinal Study, Kindergarten Class of 1998-1999, to test ideas from Lareau’s qualitative study of social class differences in parenting. Consistent with Lareau, a confirmatory factor analysis supported the general concerted cultivation construct—a parenting strategy that subsumes parents’ school engagement, children’s participation in extracurricular activities, and the amount of educational materials in the home. The authors also found that socioeconomic status (SES) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 41 publications
8
127
2
3
Order By: Relevance
“…2 Educational attainment is an important predictor of parental investment in children, with parents with more education more likely to invest in their children's human and social capital (Bianchi and Robinson, 1997). Though Lareau (2002) defines class as a function of parental occupation and finds stark differences in adherence to the "concerted cultivation" versus "natural growth" models of parenting between parents of different occupational levels, subsequent work has found that parental education is a much stronger predictor of parental investments of money and time in children than is parental occupation or parental income (Cheadle and Amato 2011).…”
Section: Contextual Effects On Parental Preferencesmentioning
confidence: 99%
“…2 Educational attainment is an important predictor of parental investment in children, with parents with more education more likely to invest in their children's human and social capital (Bianchi and Robinson, 1997). Though Lareau (2002) defines class as a function of parental occupation and finds stark differences in adherence to the "concerted cultivation" versus "natural growth" models of parenting between parents of different occupational levels, subsequent work has found that parental education is a much stronger predictor of parental investments of money and time in children than is parental occupation or parental income (Cheadle and Amato 2011).…”
Section: Contextual Effects On Parental Preferencesmentioning
confidence: 99%
“…Upper middle-class parents engage in "concerted cultivation" and more purposeful practices in daily interactions with their children. They also arrange children's daily lives and activities in more structured ways so as to enhance children's development of both cognitive and non-cognitive skills (Heckman 2006;Covay and Carbonaro 2010;Calarco 2011;Cheadle and Amato 2011;Lareau 2011). Working-class parents, in contrast, tend to intervene in children's growth at a minimal level, holding that children should grow as they are (Laureau 2011).…”
Section: Theoretical Motivation and Research Model The Fundamental Camentioning
confidence: 99%
“…Recent research in the Irish context suggests the lack of any significant relationships for child gender in relation to either child or parent behaviour 1 (Cheevers et al 2010;Halpenny et al 2010). However, in other contexts, parent's use of concerted cultivation has been found to be more pronounced among daughters than sons (Cheadle and Amato 2010 in United States).…”
Section: Gender and Concerted Cultivationmentioning
confidence: 99%
“…For this reason, parents may engage in more concerted cultivation with daughters because they are more receptive to parental influence than are sons. Alternative explanations rest on the assumption that parents may feel that more efforts are required to cultivate daughters than sons, because women have traditionally attained lower levels of education and occupational status than males, although this difference has narrowed in recent years (Cheadle and Amato 2010).…”
Section: Gender and Concerted Cultivationmentioning
confidence: 99%